Troubling Trade-offs Between Women’s Work and Intimate Partner Violence: Evidence From 19 Developing Countries - Zafar, Sameen (Journal of interpersonal violence, 2022)
The empirical link between women?s employment status and their experience of different types of intimate partner violence (IPV) is not very apparent. Using Demographic and Health Surveys (DHS) data from 19 developing countries in South Asia, Sub-Saharan Africa, and the Middle East, we found that working women were significantly more likely to experience IPV than their stay-at-home counterparts. Given the great diversity in women?s employment with respect to economic returns and working conditions, we disaggregated women?s employment into three categories vis-à-vis agriculture jobs (AJ), blue-collar jobs (BJ), and white-collar jobs (WJ). The disaggregated analysis revealed that women engaged in all three job categories were significantly more likely to experience IPV. After controlling for potential endogeneity of women?s employment, we found that women?s work increased the risk of less severe physical violence (LSPV) and emotional violence (EV) but reduced the risk of sexual violence (SV). Endogeneity-adjusted disaggregated analysis showed that women engaged in BJ and WJ faced an increased risk of LSPV but reduced risk of SV. In contrast, women undertaking AJ faced a smaller risk of severe physical violence (SPV) and SV. This study contradicts some long-held beliefs that women?s work is a sufficient condition for protecting them from IPV. The public policy should not assume that women?s earnings automatically protect them against the risk of IPV. While encouraging a greater female labor force participation rate is important in its own right, women?s risk of IPV is context-specific.